Chemoselective Transfer Hydrogenation of α,β-Unsaturated Ketones Catalyzed by Iridium Complexes - Xia, Yanping; Ouyang, Lu; Liao, Jianhua; Yang, Xiao; Luo, Renshi (SynOpen, 2021)
Efficient chemoselective transfer hydrogenation of the C=C bond of α,β-unsaturated ketones has been developed, using the iridium complexes containing pyridine-imidazolidinyl ligands as catalysts and formic acid as a hydrogen source. In comparison with organic solvents or H2O as solvent, the mixed solvents of H2O and MeOH are critical for a high catalytic chemoselective transformation. This chemoselective transfer hydrogenation can be carried out in air, which is operationally simple, allowing a wide variety of α,β-unsaturated substrates with different functional groups (electron-donating and electron-withdrawing substituents) leading to chemoselective transfer hydrogenation in excellent yields. The practical application of this protocol is demonstrated by a gram-scale transformation.
Keywords: transfer hydrogenation; iridium complex; α,β-unsaturated ketones; formic acid; chemoselective reduction